Environmental, social and governance (ESG) assessment with a two-phase goal-programming-based optimization model: a comparative study of Envipark and Kalundborg eco-industrial parks - Anelli, Debora; Morano, Pierluigi; Fariello, Francesca; Sabatelli, Emma (Frontiers in Built Environment, 2026)
IntroductionEco-industrial parks (EIPs) are key infrastructures in the transition toward circular and low-carbon production systems, yet their Environmental, Social and Governance (ESG) performance is still commonly assessed through static metrics that offer limited support for improvement strategies.MethodsThis study proposes a two-phase decision-support framework: a passive goal-programming assessment that measures gaps to regulatory targets and best practices, and an active phase that identifies cost-effective portfolios of improvement measures under budgetary and technical constraints. The framework is applied to two European EIPs, Envipark (Italy) and Kalundborg (Denmark).ResultsIn the passive phase, Envipark shows criticalities mainly in the environmental dimension, while Kalundborg achieves higher performance levels, with residual weaknesses in social indicators related to welfare and community engagement. The active phase confirms distinct strategic trajectories: Envipark tends toward incremental and demonstrative measures, whereas Kalundborg prioritises transformative, large-scale initiatives.DiscussionThe framework provides a transparent tool for policymakers and EIP managers to align investment decisions with ESG and decarbonization goals. Overall, it advances methodological practice by operationalizing goal programming for dual passive/active ESG assessment, offering a replicable framework for EIPs, and bridging the gap between assessment and decision-making in sustainability governance.